The Impact of Using Youtube on Developing Kurdish EFL University Students’ Speaking Skills - Zanyar Nathir Ghafar; Sozyar Raza Ali; Hemn Mohammed Ali (RADINKA JAYA UTAMA PUBLISHER, PADANG< INDONESIA, 2025)
This study investigates the impact of YouTube on the development of English-speaking skills among Kurdish EFL university students and graduates. The research aimed to evaluate how YouTube's digital pedagogy influences oral proficiency, learner confidence, and autonomous learning strategies. Using a descriptive mixed-methods design, data were gathered from 32 participants via convenience sampling in the Kurdistan Region. The primary instrument was a 17-item online questionnaire analyzed through descriptive statistics and thematic content analysis. The findings indicate that YouTube functions as a potent catalyst for psychological and linguistic development, markedly increasing speaking confidence and diminishing language anxiety. The findings indicate that students effectively acquire skills incidentally through entertainment and strategically utilize subtitles as cognitive scaffolding. The study concludes that YouTube successfully bridges the gap between formal instruction and real-world communication, implying that integrating multimedia platforms into EFL curricula can foster greater learner autonomy and global intelligence.